Discovery and screening of novel metagenome‐derived GH107 enzymes targeting sulfated fucans from brown algae. (8th October 2018) - Schultz‐Johansen, Mikkel; Cueff, Marie; Hardouin, Kévin; Jam, Murielle; Larocque, Robert; Glaring, Mikkel A.; Hervé, Cécile; Czjzek, Mirjam; Stougaard, Peter
Abstract : Sulfated fucans, often denoted as fucoidans, are highly variable cell wall polysaccharides of brown algae, which possess a wide range of bioactive properties with potential pharmaceutical applications. Due to their complex architecture, the structures of algal fucans have until now only been partly determined. Enzymes capable of hydrolyzing sulfated fucans may allow specific release of defined bioactive oligosaccharides and may serve as a tool for structural elucidation of algal walls. Currently, such enzymes include only a few hydrolases belonging to the glycoside hydrolase family 107 (GH107), and little is known about their mechanistics and the substrates they degrade. In this study, we report the identification and recombinant production of three novel GH107 family proteins derived from a marine metagenome. Activity screening against a large substrate collection showed that all three enzymes degraded sulfated fucans from brown algae in the order Fucales. This is in accordance with a hydrolytic activity against α‐1, 4‐fucosidic linkages in sulfated fucans as reported for previous GH107 members. Also, the activity screening gave new indications about the structural differences in brown algal cell walls. Finally, sequence analyses allowed identification of the proposed catalytic residues of the GH107 family. The findings presented here form a new basis for understanding the GH107 family of enzymes and investigating the complex sulfated fucans from brown algae. Database: The assembled metagenome and raw sequence data is available at EMBL‐EBI (Study number:PRJEB28480 ). Sequences of the GH107 fucanases (Fp273, Fp277, and Fp279) have been deposited in GenBank under accessionsMH755451 –MH755453 . Abstract : Enzymes belonging to the GH107 family degrade sulfated fucans—complex polysaccharides found in brown macroalgae. However, currently very few members have been identified. This study describes the discovery of three new GH107 fucanases, verified by sequence and functional analyses. The work will aid in further understanding the structure of brown algal polysaccharides and the hydrolytic mechanisms involved in their degradation.